PENERAPAN KONSELING INDIVIDUAL UNTUK MENGATASI PERMASALAHAN PERILAKU BELAJAR PESERTA DIDIK KELAS VII SEKOLAH MENENGAH PERTAMA - Baina Mardia (Journal of Social Studies, Arts and Humanities (JSSAH), 2022)
APPLICATION OF INDIVIDUAL COUNSELING TO OVERCOME LEARNING BEHAVIOR PROBLEMS FOR GRADE 7 JUNIOR HIGH SCHOOL STUDENTSThis research is motivated by the high problem of student learning behavior, including the habit of truancy during class hours, not going to school without information, not paying attention when the teacher teaches, not doing homework, and forgetting other school assignments. Therefore, researchers will make efforts to overcome the problems of student learning behavior through the application of individual counseling in the hope that students will be able to improve their behavior in following the learning process. The purpose of this study was to determine the application of individual counseling to overcome behavioral problems, describe the improvement of the process in overcoming learning behavior problems, measure the magnitude of the increase in the process of overcoming students' learning behavior problems by applying individual counseling in class VII Junior High School. The method used is action research. The research is carried out in two cycles, the second cycle is very dependent on the impact or results of giving actions in the first cycle. The results of the reflection in the first cycle revealed deficiencies and were followed up and included in the planning of the second cycle. The Guidance and Counseling Action Research design used was the Kemmis Mc. Taggart. The results of the study show that the implementation of guidance and counseling with an individual counseling approach can overcome the problems of learning behavior of students in class VII Junior High School. There is an increase in the ability of students in an effort to overcome learning behavior problems and is supported by the active involvement of students in the implementation of individual counseling. The magnitude of the increase in efforts to overcome the problems of student learning behavior can be seen from the lowest score in the pre-cycle, which was 38, increasing to 65 in the first cycle and 85 in the second cycle. In the pre-cycle nothing was completed in overcoming the problem of learning behavior, then in the first cycle it increased to 58.33% or 7 students whose scores were above the minimum score then in the second cycle it became 100.00% or 12 students whose scores were above minimum score.